Intramuscular hemangioma in buccal cheek: a case report - Park, Jae Woo (J Korean Assoc Oral Maxillofac Surg, 2017)
Hemangioma is the most common benign tumor of a vascular origin, and is characterized by the abnormal proliferation of blood vessels. Intramuscular hemangioma (IMH) usually involves the skeletal muscles of the trunk or limbs, but rarely occurs in the head and neck region. This case report presents a patient with IMH showing multiple phleboliths in the buccal cheek. A 13-year-old boy was referred for the evaluation and management of painful swelling of the left cheek that had gradually increased in size over a 6 year duration. The examination revealed a palpable firm mass. Reddish-blue buccal mucosa color was observed with an aciniform shape. Preoperative magnetic resonance imaging (MRI) showed a vascular tumor in the left side adjacent to the buccinator and depressor orbicularis oris muscles. Surgical resection under general anesthesia was performed via the intraoral approach. The mass and phleboliths were extracted successfully. A histopathological examination confirmed the diagnosis of IMH. In conclusion, clinicians should be aware of the possibility of IMH in cases of a palpable mass with multiple nodules deep within the muscle in the buccal cheek. Among the several diagnostic tools, MRI provides essential information on the extent and surrounding anatomy of IMH.